Vous êtes sur la page 1sur 31

Solutions Manual for

Advanced Microeconomic Theory I


Jianfei Shen
School of Economics, Shanghai University of Finance and Economics

E-mail address: jianfeishen@163.com


URL: http://www.shufe.edu.cn

Thanks.

Contents
Part 1.

Consumer Theory

Chapter 1. Solution for Exercise I


1. (JR, 1.4)
2. (JR, 1.27)
3. (JR, 1.56)
4. (JR, 1.24)
5. (Homogeneity)

3
3
3
4
5
6

Chapter 2. Solution for Exercise II


1. (JR, 1.36)
2. (JR, 2.10)
3. (MWG, 2.F.7)
4. (JR, 1.62)
5. (JR, 2.9)

9
9
9
10
11
11

Part 2.

13

Production and Choice under Uncertainty

Chapter 3. Solution for Exercise III


1. (JR, 3.36)
2. (JR, 3.39)
3. (The Allais Paradox)
4. (The Simplex)
5. (Independence Axiom)

15
15
16
17
18
19

Chapter 4. Solution for Exercise IV


1. (MWG, 6.C.16)
2. (MWG, 6.C.20)
3. (Betweenness Axiom)
4. (Quadratic v.N-M Utility Function)

21
21
22
23
24

Part 1

Consumer Theory

CHAPTER 1

Solution for Exercise I


1. (JR, 1.4)
L
Proof. Suppose that x, y, z R+
, and x  y, y  z. By Definition 1.21,
we have

x  y x < y y  x;

(1.1)
and

y  z y < z z  y.

(1.2)

The transitivity implies that x < z. Suppose that z < x. Since y < z [by equation
(1.2)], the transitivity then implies that y < x. But this contradicts (1.1). Thus
z  x. Hence
x  z.
Suppose x y, and y z. By Definition 1.32, we have
x y x < y y < x;

(1.3)
and

y z y < z z < y.

(1.4)
The transitivity implies that

x<z

and z < x.

Hence
x z.

2. (JR, 1.27)
Solution. If x1 < x2 ,
u(x) = max[ax1 , ax2 ] + min[x1 , x2 ] = ax2 + x1 ;
If x2 < x1 ,
u(x) = max[ax1 , ax2 ] + min[x1 , x2 ] = ax1 + x2 .
Case i: a <

p1
p2

< a1 . In this case,


x1 = x2 =

1Jehle & Reny, 2001, P6


2Jehle & Reny, 2001, P7
3

w
.
p1 + p 2

1. SOLUTION FOR EXERCISE I

x2

C
O

x1

Figure 2.1. The Indifference Curve


Case ii:

p1
p2

> a1 . In this case, there is a corner solution


x1 = 0, x2 =

Case iii:

p1
p2

< a. In this case, there is a corner solution, too


x1 =

Case iv:

p1
p2

p1
p2

w
, x2 = 0.
p1

= a1 . In this case, the UMP is


x1 =

Case v:

w
.
p2



w p2 x2
w
w
, x2
,
.
p1
p 1 + p2 p 2

= a. In this case, the UMP is


x1 =



w p2 x2
w
, x2 0,
.
p1
p1 + p2

3. (JR, 1.56)

Solution. Use the monotone transformation of the given utility function3:


v(x) = ln u(x) =

n
X

bi ln(xi ai ).

i=1

The UMP can written as


max
s.t.

n
X

bi ln(xi ai );

i=1
n
X

pi xi w.

i=1
3Stone, J.E. (1954): Linear Expenditure Systems and Demand Analysis: An Application to
the Pattern of British Demand. Economic Journal 64: 51127

4. (JR, 1.24)

Then form the Lagrangian, we obtain


L =

n
X

bi ln(xi ai ) + w

i=1

n
X

!
pi xi

i=1

The first-order condition of the UMP yields


bi
L
=
pi = 0,
(1.5)
xi
xi ai
Summarize all of the first-order conditions:
n
X
(1.6)
1=
pi (xi ai ) = Pn

i.

1
.
p
(xi ai )
i
i=1

i=1

With (1.5) and (1.6), we have


pi (xi ai )
pi (xi ai )
Pn
bi = Pn
=
.
w i=1 pi ai
i=1 pi (xi ai )
So
xi = ai +

bi (w

Pn

i=1

pi ai )

pi

i.


4. (JR, 1.24)
Solution. A utility function that represents a preference relation < is not
unique. For any strictly increasing function: f : R R, v(x) = f (u(x)) is a new
utility function representing the same preferences as u()4.
a: f (x) = u(x) + [u(x)]2 .
f ()
= 1 + 3[u(x)]2 > 0.
u()
So this is a strictly increasing function, and it represents thesame <.
b: f (x) = u(x) + [u(x)]2 .
f ()
= 1 + 2u(x).
u()
f ()
u()

0 if u(x) 12 . In this case, f (x) does not represents the


same <;
f ()
u()
> 0 if u(x) > 12 . In this case, f (x) represents the same <.
Pn
c: f (x) = u(x) + i=1 xi .
Not necessarily. f represents
Pn the same preferences as u if u(x) is a
monotonic transformation of i=1 xi . Otherwise, they may not represent
the same preferences. For example, suppose u(x) = x1 . Then

u(1, 0, . . . , 0) > u(0, 3, 0, . . . , 0),


but
f (1, 0, . . . , 0) = 1 + 1 = 2 < 3 = 0 + 3 = f (0, 3, 0, . . . , 0).

4Let x, y R L .
+

Since u() represents <, x < y iff u(x) u(y). Since f () is strictly
increasing, u(x) u(y) iff v(x) v(y). Hence x < y iff v(x) v(y). Therefore v() represents <.
This completes the proof.

1. SOLUTION FOR EXERCISE I

5. (Homogeneity)
L
L
Proof. a: We want to show that p R++
, y 0, 0, and x R+
, if x
is the Marshallian demand at (p, y), then x0 = x is the Marshallian demand at
(p, y). Well complete this proof with two steps:

Step I: we prove that the consumption bundle x0 is affordable at (p, y).


Note that p x y p y y, so x0 = x is affordable at (p, y) indeed.
Step II: we prove that the consumption bundle x0 is the Marshallian demand
function at (p, y).
L
Let x00 R+
and p x00 y. Then

p
Hence

x00
y.


x00
< u(x), (by the Strictly quasiconcave)

since x is the Marshallian demand function at (p, y).


Thus, by the homogeneity of u():
 00 
1
x
= u (x00 ) < u(x) u(x00 ) u(x) = u(x).
u

Hence x is the Marshiallian demand function at (p, y), and


x(p, y) = x(p, y).
b: By the result of part (a), we have
v(p, y) = u(x(p, y)) = u( x(p, y)) = u(x(p, y)) = v(p, y).
This proves that the indirect utility function v() is homogeneous of degree one in
y.
L
and 0, we have u(x) = u(x).
c: In this part, well show that x R+
We first prove that
x(p, y) = x(p, y),
where x() is the Marshiallian demand function.
Since v(, ) is homogeneous of degree one in y:
v(p, y) = v(p, y),
we have
p v(p, y) = p v(p, y),
and
y v(p, y) = y v(p, y) = y v(p, y) y v(p, y) = y v(p, y).
Then by Roys identity:
xi (p, y) =
we have
x(p, y) =

v(p, y)/pi
,
v(p, y)/y

i = 1, . . . , L,

p v(p, y)
p v(p, y)
=
= x(p, y).
y v(p, y)
y v(p, y)

5. (HOMOGENEITY)

Now, again by the homogeneity of v(, ), we have


u( x(p, y)) = u(x(p, y)) = v(p, y) = v(p, y) = u(x(p, y)).
This completes the proof of
u( x(p, y)) = u(x(p, y)).


CHAPTER 2

Solution for Exercise II


1. (JR, 1.36)
Solution. a. By definition,
e(p, u) , min p x
L
xR+

s.t. u(x) u
The solution to the EMP is known as the Hicksian demand function: h(p, u). Hence
u(x0 ) u0 ,
and so
e(p, u0 ) p x0 ,
with the equality sign holds when p = p0 .
b. It follows immediately from part a that
f (p) = e(p, u) p x0
is maximized at p = p0 :
max f (p) = 0.
c. If f (p) is differentiable at p0 ,

p f p0 = 0.

(2.1)

d. If e(p, u) is differentiable in p, then by equation (2.1) we have


p f = p e x0 = 0,
so
h(p, u) = p e(p, u).

2. (JR, 2.10)
Solution. a.

Price

p0
p1
p2

x0
42
33
52
9

Bundle
x1
x2
48
40
36 39()
48
51

10

2. SOLUTION FOR EXERCISE II

These consumption bundles are plausible in that the WARP is satisfied. In particular, we note
p1 x1 = 36 > 33 = p1 x0 ,
p0 x0 = 42 < 48 = p0 x1 ,
so
x1 Rx0 .

(2.2)

p0 x0 = 42 > 40 = p0 x2 ,
p2 x2 = 50 < 52 = p2 x0 ,
so
x0 Rx2 .

(2.3)

p2 x2 = 50 > 48 = p2 x1 ,
p1 x1 = 36 < 39 = p1 x2 ,
so
x2 Rx1 .

(2.4)

b. Now, from (2.2) and (2.3) we have


x1 Rx0 ,

x0 Rx2 ;

but from (2.4), something utterly revolting occurs:


x2 Rx1 .
So the revealed preference R is intransitivity.

3. (MWG, 2.F.7)
Proof. If the Walrasian demand function x(p, w) satisfies Walras law, then
for all p and w:
(2.5)

L
X
`=1

p`

x` (p, w)
+ xk (p, w) = 0,
pk

k = 1, . . . , L,

or
p Dp x(p, w) + x(p, w)0 = 00

(2.6)
and

L
X

(2.7)

`=1

p`

x` (p, w)
= 1,
w

or
p Dw x(p, w) = 1.

(2.8)

If the Walrasian demand function x(p, w) is h.o.d. 0, then for all p and w:
(2.9)

L
X
x` (p, w)
k=1

pk

pk +

x` (p, w)
w = 0,
w

` = 1, . . . , L,

or
(2.10)

Dp x(p, w)p + Dw x(p, w)w = 0.

5. (JR, 2.9)

11

By the Slutsky Equation:


h` (p, u)
x` (p, w) x` (p, w)
=
+
xk (p, w),
pk
pk
w

(2.11)

`, k

or equivalently,
(2.12)

Dp h(p, u) = Dp x(p, w) + Dw x(p, w)x(p, w)0 ,

where Dp h(p, u) is equal to the matrix

s11 (p, w)

..
S(p, w) =
.

s1L (p, w)

..

..
.
sL1 (p, w)

sLL (p, w)

with
s`k (p, w) =

x` (p, w) x` (p, w)
xk (p, w).
+
pk
w

So we have
p S(p, w) = p Dp x(p, w) + p Dw x(p, w)x(p, w)0
0

= p Dp x(p, w) + x(p, w)

(2.13)

=0,

[from (2.12)]

[from (2.8)]

[from (2.6)]

and
S(p, w)p = Dp x(p, w)p + Dw x(p, w)x(p, w)0 p
(2.14)

= Dp x(p, w)p + Dw x(p, w)w

[from (2.12)]

[from Walras law]

= 0. [from (2.10)]

4. (JR, 1.62)
Solution. Since
p S(p, w) = 0,
S(p, w)p = 0
and by symmetric, we have
a = 8,

b = 2,

p = 32.


5. (JR, 2.9)
Proof. a. In the case of two goods, equation (2.13) can be written as



 s11 (p, w) s12 (p, w)
p S(p, w) = p1 p2
s21 (p, w) s22 (p, w)


(2.15)
= p1 s11 (p, w) + p2 s21 (p, w) p1 s12 (p, w) + p2 s22 (p, w)


= 0 0 .
From equation (2.15) we have
s21 (p, w) =

p1
s11 (p, w),
p2

12

2. SOLUTION FOR EXERCISE II

and
s12 (p, w) =

p2
s22 (p, w).
p1

And the equation (2.14) becomes



 
s (p, w) s12 (p, w) p1
S(p, w)p = 11
s21 (p, w) s22 (p, w) p2


p s (p, w) + p2 s12 (p, w)
= 1 11
(2.16)
p1 s21 (p, w) + p2 s22 (p, w)
 
0
=
.
0
From equation (2.16) we have
s12 (p, w) =

p1
s11 (p, w),
p2

s21 (p, w) =

p2
s22 (p, w).
p1

and
Thus

s12 (p, w) = s21 (p, w).




Part 2

Production and Choice under


Uncertainty

CHAPTER 3

Solution for Exercise III


1. (JR, 3.36)
Proof. We can get some intuition from the following figure 1.
x2

tx02
x02
O

B
A
y
x01

y1

tx01

x1

Figure 1.1. Homothetic production function


Now we give the regular proof. The cost function for all homothetic production
function can be written
(3.1)

c(w, y) = h(y)(w),

where (w) is linear homogeneous. 1


Then using the Shephards Lemma 2, we have
c(w, y)
xi (w, y) =
= h(y)i (w),
wi
c(w, y)
xj (w, y) =
= h(y)j (w).
wj
Hence
xi (w, y)
i (w)
(3.2)
=
, (w),
xj (w, y)
j (w)
that is,
(xi (w, y)/xj (w, y))
= 0.
y
1Any cost function is linear homogeneous in the factor prices.
2JR, Theorem 3.2, p.129
15

16

3. SOLUTION FOR EXERCISE III


2. (JR, 3.39)
Proof. a: If the production function is CRS, then
n
X
c(w, y) =
wi xi (w, y)
i=1

n
X

fi xi (w, y)

i=1
n
X

[ From the F.O.C. ]

xi (w, y) fi

i=1

= y

[ From the Euler Equation ]

c(w, y)
y
=
y

[ By the interpretation of ]

or
c(w, y)
y
=
.
c(w, y)
y

(3.3)

Solve the partial differential equation (3.3), we get


(3.4)

c(w, y) = y(w),

where (w) is a function of factor prices w only.


b: If c(w, y) = y(w), then from the F.O.C. of the cost minimization problem
that for x(w, y) > 0
(3.5)

wi = fi ,

and
(3.6)

c(w, y)
.
y

Combine equation (3.5) and (3.6), we obtain


wi = (w)fi ,
or
xi fi =

wi xi
.
(w)

Hence, for all xi (w, y)


n
X

xi fi =

i=1

n
X
wi xi
(w)
i=1
n

1 X
wi xi
(w) i=1

c(w, y)
(w)
y(w)
=
(w)
= f (x).
=

3. (THE ALLAIS PARADOX)

17

It follows from the Eulers Theorem 3 that


(3.7)

f (tx) = tf (x),

that is, the production function is CRS.



3. (The Allais Paradox)
Proof. Defining
X = {x1 , x2 , x3 } = {$ 0; $ 1, 000, 000; $ 5, 000, 000},
these four gambles are seen form a parallelogram in the (p1 , p3 ) triangle, as in the
following figure.
1

p3

p3
g2

g3

g1

p1 g4

g2

g1

(a)

g3

p1 g4
(b)

Figure 3.1. Indifference curves and the Allais Paradox


The Independence Axiom is in fact equivalent to linearity in the probabilities.
IA implies that:
(1) Indifference curves are straight lines: if, g, g 0 G , we have
g g0
implies
g + (1 )g = g g 0 + (1 )g,

(0, 1).

(2) Indifference curves are parallel lines: if, g, g 0 , g 00 G , we have


g g0 ,
the IA implies that
g + (1 )g 00 g 0 + (1 )g 00 ,

3Eulers Theorem: f (x) is homogeneous of degree r iff


n

rf (x) =

i=1

xi f i .

(0, 1).

18

3. SOLUTION FOR EXERCISE III

Now consider the conditions in the Allais Paradox. A preference for g1 in


the first pair gambles would indicate that the individuals indifference curves were
relatively steep, and hence a preference for g4 in the second pair.4
If, on the contrary, g1 is preferred in the first pair, and g3 in the second, which
implies that indifference curves are parallel but rather fan out, as in figure (b).
Now we turn to do the job follows another way. We can rewrite the gambles
as
g1 = (0.10 1, 0.01 1, 0.89 1);
g2 = (0.10 5, 0.01 0, 0.89 1);
g3 = (0.10 5, 0.01 0, 0.89 0);
g4 = (0.10 1, 0.01 1, 0.89 0).
Consider the following three gambles
g5 = Get 1 with

0.10
g6 =
5,
0.11
g7 = Get 0 with

certainty;

0.01
0 ;
0.11
certainty.

By the Completeness Axiom, we know either g5 < g6 or g6 < g5 .


(1) If g5 < g6 : by the IA, we have
0.11g5 + 0.89g5 < 0.11g6 + 0.89g5 ,
or
g1 < g2 ;
and
0.11g5 + 0.89g7 < 0.11g6 + 0.89g7 ,
or
g4 < g3 .
(2) If g6 < g5 : we can do the job with the same logic as part (1), and get
g2 < g1 ,
and
g3 < g4 .

4. (The Simplex)
Solution. The slope: Keeping the level of v.N.M utility constant
p1 u(x1 ) + p2 u(x2 ) + (1 p1 p2 )u(x3 ) = Const.,
and varying p1 and p2 alone, one has, locally,
dp2
dp2
u(x1 ) +
u(x2 ) + (1
)u(x3 ) = 0,
dp1
dp1
or
dp2
u(x3 ) u(x1 )
=
0,
dp1
u(x2 ) u(x3 )
4In the alternative case of relatively flat indifference curves, the gambles g and g would be
2
3
preferred.

5. (INDEPENDENCE AXIOM)

19

since x2 > x3 > x1 .


Direction where the utility increasing: Since upward movements in the
triangle increase p2 at the expense of p3 (i.e. shift probability from the outcome x3
up to x2 ) and leftward movements reduce p1 to the benefit of p3 (shift probability
from x1 to x3 ), these movements (and more generally, all northwest movements)
lead to stochastically dominating gambles and would accordingly be preferred.
1

p2

p1

Figure 4.1. Expected utility indifference curves in the simplex diagram


5. (Independence Axiom)
Proof. Let us assume without loss of generality that the elements of A have
been indexed so that
a1 < a2 < < an .
Now, let gk , 0 k n, be the gamble that yields outcome k with probability
one:
gk = (0 a1 , 0 a2 , . . . , 1 ak , . . . , 0 an ).
Then
a1 < gk < an ,
since all of them can be identified with sure outcomes.
Let
g = (p1 a1 , . . . , pn an )
be any gamble in G , then
n
X
g=
pk gk .
k=1

If there is only one k, s.th. pk = 1, that is, pj = 0, j 6= n, there is nothing to


prove. So let
N = #{(1, . . . , n) : pk 6= 0, 0 k n} > 1

20

3. SOLUTION FOR EXERCISE III

and suppose the proposition


a1 <

N
1
X

pk gk < an

k=1

is true for N 1. By the definition of a compound gamble,


N
X

pk gk = (1 pN )

k=1

N
1
X
k=1

pk
gk + pN gN .
1 pN

By the induction hypothesis,


a1 < (1 pN )

N
1
X
k=1

pk
gk < an .
1 pN

Hence, by the independence axiom, we have


(1 pN )a1 + pN gN < (1 pN )

N
1
X
k=1

pk
gk + pN gN < (1 pN )an + pN gN .
1 pN

Applying the axiom once again, we obtain


a1 = (1 pN )a1 + pN a1 < (1 pN )a1 + pN gN ;
(1 pN )an + pN gN < (1 pN )an + pN an = an .
Hence, by the transitivity,
a1 < g < an , g G .


CHAPTER 4

Solution for Exercise IV


1. (MWG, 6.C.16)
Solution. The maximum amount the person is willing to buy the
gamble:
(4.1)

0.5u(w Rb y) + 0.5u(w Rb + x) = u(w),

where Rb is the maximal buying price.


u()

u(w)

Rb

Rb

wy

w+x

Figure 1.1. The maximum amount the person is willing to buy


the gamble

The minimum amount the person is willing to sell the gamble:


(4.2)

0.5u(w y) + 0.5u(w + x) = u(w + Rs ),

where Rs is the minimal selling price.


In general, these two prices are different. However, if u() is CARA, then they
are the same. In face, equation (4.1) and (4.2) can be restated as
(4.3)

CEwRb = w,

(4.4)

CEw = w + Rs ,
21

22

4. SOLUTION FOR EXERCISE IV

u()

E[u()]
u(w)

Rs

wy

w w + Rs

w+x

Figure 1.2. The minimum amount the person is willing to sell


the gamble

where CEwRb and CEw are certainty equivalence for (4.1) and (4.2), respectively.
The CARA implies that1
(w Rb ) CEwRb = w CEw ,
thus
Rb = Rs .

2. (MWG, 6.C.20)
Proof.
u(CE) = 0.5u(x + ) + 0.5u(x ),
where CE is the Certainty Equivalent. Hence
u0 (CE)

(4.5)

(4.6)

u00 (CE)

CE

CE
= 0.5u0 (x + ) 0.5u0 (x ),

2

+ u0 (CE)

2 CE
= 0.5u00 (x + ) + 0.5u00 (x ).
2

Thus
0.5u00 (x + ) + 0.5u00 (x ) u00 (CE)
2 CE
=
lim
lim
0
0 2
u0 (CE)
00
u (x)
= 0
u (x)
= Ra (x),
1See MWG (1995) Section 6.C.


CE 2

3. (BETWEENNESS AXIOM)

23

since
lim
0

CE
0.5u0 (x + ) 0.5u0 (x )
= lim
0

u0 (CE)
= 0,

and
lim u(CE) = u(x).
0


3. (Betweenness Axiom)
Solution. The Betweenness Axiom 2 only requires that indifference sets be
convex, i.e., if an individual is indifferent between two lotteries, then any probability
mixture of these two is equally good: if g g 0 , then
g + (1 )g 0 g,

[0, 1].

Essentially, the betweennss axiom is a substantially weaker version of the controversial independence axiom. 3
The axioms 1-4, 6, and the betweenness axiom means that the indifference
curves are straight lines can be established in the same way as in Chapter 3, exercise
(3). Note that we do not use the independence axiom in that exercise, in fact,
betweenness axiom is suffices.
Note also that these straight indifference curves need not be parallel, because
the betweenness axiom imposes restrictions only on straight indifference curves and
nothing on the relative positions of different indifference curves.
1

p2

p1

Figure 3.1. Betweenness axiom means the indifference curves


are straight lines, but need not be parallel.


2See Dekel, E. (1986) for further discussion.
3See MWG Exercise 6.B.1A .

24

4. SOLUTION FOR EXERCISE IV

4. (Quadratic v.N-M Utility Function)


a.
Solution. The restrictions are
u0 (w) > 0,

u00 (w) < 0,

so
b > 4cw;

c < 0.

b.
Solution.
Ra (w) =
so

4c
,
b + 4cw

Ra (w)
16c2
=
w
(b + 4cw)2
> 0.
This means that the quadric utility functions are unsatisfactory. Not only do
they imply that utility reaches a maximum, they also entail that the absolute degree
of risk aversion is increasing in wealth, approaching infinity as utility approaches
its maximum. Consequently, one is led to the absurd result that the willingness to
gamble for a bet of fixed size should decrease as wealth is increased.

c.
Proof. Before going through the proof, it is worthwhile to consider the intuition of the representation. The expected utility hypothesis suggests that preferences toward gambles can be represented by the expected value of a v.N-M utility
function


E u(w) ,
where w is a random variable that represents the income from an uncertain gamble.
Expected utility in general depends on the form of the function u() and on the
distribution of w. Suppose the distribution of w can be completely characterized
by a vector of parameters . In particular, let w be distributed on the real line
with a P.D.F. f (w, ). Then4
Z


E u(w) = u(w)f (w, ) dw.
The integral on the right-hand side of this equation is a function of .5 If we let
this integral be represented by
u(),
then


u() = E u(w)
is a valid representation of preferences.
4From this subsection through the end of the chapter, we focus on continuous monetary
variable for convenience.
5It is not a function of w since w is just the variable of integration.

4. (QUADRATIC V.N-M UTILITY FUNCTION)

25

Many problems in the economics of uncertainty are related to the trade-off


between the average level of income and its degree of riskiness. Since the mean is
a summary measure of average and the variance is a summary measure of risk, it
will be particularly convenient to represent preferences by a function of the mean
and variance of the income distribution. Unfortunately, this is not always possible,
because in general the mean and variance do not completely determine the distribution of a random variable. There are many income streams that have the same
mean and variance but different probability distributions. The expected utility
associated with these income streams are different. Although u() is a valid representation of preferences, the vector generally contains more than two parameters.
Thus a utility function that depends only on mean and variance can be at best be
viewed as an approximation to expected utility.
There are some special cases, however, when a function involving only the mean
and variance of the income distribution can be used to represent preferences. The
quadratic utility function in this exercise is a such example.


 
 
E u(w) = a + bE w + 2cE w2
 
   2
 
= a + bE w + 2c E w
+ 2cVar w .

d.

Solution. We prove this proposition by an indifference curve in the meanvariance plane.7 To establish this result, consider two gambles g1 , g2 G such
that
g1 g2 .
Then, the individual must be indifferent between g1 , g2 , and a compound gamble
gq = (q g1 , (1 q) g2 ),

q [0, 1]

where q denotes the probability of obtaining g1 , and consequently (1 q) is the


probability of obtaining g2 .
gq g1 g2 .
Letting i and i2 denote the mean and variance, respectively, of the distributions corresponding to the gambles (i = 1, 2, and q).

6Markowitz (1959) demonstrated that if the ordering of alternatives is to satisfy the v.N-M
axioms of rational behavior, only a quadratic utility function is consistent with an ordinal expected
utility function that depends solely on the mean and variance of the return. Consequently, even
if the return for each alternative has a normal distribution, the mean-variance framework cannot
be used to rank alternatives consistently with the v.N-M axioms unless a quadratic v.N-M utility
function is specified.
7Our proof gives here follows Baron (1977).

26

4. SOLUTION FOR EXERCISE IV

V (, 2 ) =
2

g2

q
1

gq
g1

12

q2

22

Figure 4.1. An indifference curve in the mean-variance plane.


Note that distribution functions preserve the linear structure of gambles (as do
P.D.F.s),8 so
Z


q = w d qF1 (w) + (1 q)F2 (w)
Z
Z
(4.7)
= q w dF1 (w) + (1 q) w dF2 (w)
= q1 + (1 q)2 .
q2 =
(4.8)


2 

w q1 (1 q)2 d qF1 (w) + (1 q)F2 (w)


2 

q(w 1 ) + (1 q)(w 2 ) d qF1 (w) + (1 q)F2 (w)

= q12 + (1 q)22 + q(1 q)(1 2 )2 .


Solving for q from (4.7) yields
(4.9)

q=

q 2
.
1 2

Substituting (4.9) into (4.8) yields




 2 1 (1 2 ) + 2 12 1 22
1 2
q
2q + q2 =
,
2
2
2
2
1 2 + 1 2
21 22 + 12 22
or

(4.10)
q 2q + q2 = k,
where
1 2
,
21 22 + 12 22
2 1 (1 2 ) + 2 12 1 22
k=
.
21 22 + 12 22

8See MWG (1995) p.183.

4. (QUADRATIC V.N-M UTILITY FUNCTION)

27

We can rewrite equation (4.10) again


(4.11)


a + bq + c 2q + q2 = ,

where the parameters (a, b, c, ) satisfy


c
= ,
b
a
= k.
b
Equation (4.11) implies that
Z

V (q , q2 ) = a + bq + c 2q + q2 = (a + bw + cw2 )d Fq (w).
So the v.N-M utility function that corresponds to V (, 2 ) is the quadratic
function
u(w) = a + bw + cw2 .